2018
DOI: 10.1155/2018/3457196
|View full text |Cite
|
Sign up to set email alerts
|

Bioremoval of Different Heavy Metals by the Resistant Fungal StrainAspergillus niger

Abstract: The objective of this work was to study the resistance and removal capacity of heavy metals by the fungus Aspergillus niger. We analyzed the resistance to some heavy metals by dry weight and plate: the fungus grew in 2000 ppm of zinc, lead, and mercury, 1200 and 1000 ppm of arsenic (III) and (VI), 800 ppm of fluor and cobalt, and least in cadmium (400 ppm). With respect to their potential of removal of heavy metals, this removal was achieved for zinc (100%), mercury (83.2%), fluor (83%), cobalt (71.4%), fairly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…As co-adaptation between plants and its rhizospheric soil microbiota is essential to cope with edaphic stresses under extreme environment, the observed higher abundance of members of phylum Ascomycota belonging to class Dothideomycetes and Eurotiomycetes imply they could be playing important roles in the ecology and stability of P. australis under such extreme environment. Several studies have reported that filamentous fungal genera such as Aspergillus , Mucor , and Trichoderma [ 52 , 53 , 54 ], Rhodotorula [ 55 ], Rhizopus [ 56 ], and Penicillium [ 57 ] are adaptable to environmental heavy metal contamination, detoxify them through inherent mechanisms such as transformation, crystallization, extracellular precipitation, complexation, and cellular absorption [ 57 , 58 , 59 ]. In this study, members of genera Penicillium , Candida , Saccharomycetales , Vishniacozyma , Trichoderma , Cladosporium , and unclassified Didymellaceae were highly enriched in the root endosphere and rhizospheric samples from AMD sites compared to the non-AMD site ( Figure 3 c).…”
Section: Discussionmentioning
confidence: 99%
“…As co-adaptation between plants and its rhizospheric soil microbiota is essential to cope with edaphic stresses under extreme environment, the observed higher abundance of members of phylum Ascomycota belonging to class Dothideomycetes and Eurotiomycetes imply they could be playing important roles in the ecology and stability of P. australis under such extreme environment. Several studies have reported that filamentous fungal genera such as Aspergillus , Mucor , and Trichoderma [ 52 , 53 , 54 ], Rhodotorula [ 55 ], Rhizopus [ 56 ], and Penicillium [ 57 ] are adaptable to environmental heavy metal contamination, detoxify them through inherent mechanisms such as transformation, crystallization, extracellular precipitation, complexation, and cellular absorption [ 57 , 58 , 59 ]. In this study, members of genera Penicillium , Candida , Saccharomycetales , Vishniacozyma , Trichoderma , Cladosporium , and unclassified Didymellaceae were highly enriched in the root endosphere and rhizospheric samples from AMD sites compared to the non-AMD site ( Figure 3 c).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the bioremoval mechanisms of heavy metals by some fungal species has been partially studied ( Figures 2 , 3 ) and the efficiency of such fungal species to remove heavy metals determined. But still, some mechanisms are not well understood ( Suhasini et al, 1999 ; Taştan et al, 2010 ; Mathew et al, 2016 ; Acosta-Rodríguez et al, 2018 ). The sophisticated cell wall structure profoundly influences the biosorption of heavy metals by fungal species ( Table 1 ).…”
Section: Biosorption Mechanisms Of Heavy Metals By Microbiotamentioning
confidence: 99%
“…Lab-scale and greenhouse experiments validate soil HM mycoremediation performance [ 24 , 31 , 39 ]. Similarly, effective recovery of HMs from contaminated water by fungi as biosorbents has also been demonstrated at small-scales [ 45 , 46 , 47 , 48 ]. Fungal biosorbents were extensively studied by previous researchers [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, effective recovery of HMs from contaminated water by fungi as biosorbents has also been demonstrated at small-scales [45][46][47][48]. Fungal biosorbents were extensively studied by previous researchers [46][47][48][49][50][51][52]. However, the complexity of the biosorption process, development, and cost effectiveness of adequate techniques for large-scale application await further research and deliberation prior to industrial transfer [53,54].…”
Section: Introductionmentioning
confidence: 99%